Targeting calcium regulators as therapy for heart failure: focus on the sarcoplasmic reticulum Ca-ATPase pump - Kho, Changwon (Frontiers in Cardiovascular Medicine, 2023)
Impaired myocardial Ca2+ cycling is a critical contributor to the development of heart failure (HF), causing changes in the contractile function and structure remodeling of the heart. Within cardiomyocytes, the regulation of sarcoplasmic reticulum (SR) Ca2+ storage and release is largely dependent on Ca2+ handling proteins, such as the SR Ca2+ ATPase (SERCA2a) pump. During the relaxation phase of the cardiac cycle (diastole), SERCA2a plays a critical role in transporting cytosolic Ca2+ back to the SR, which helps to restore both cytosolic Ca2+ levels to their resting state and SR Ca2+ content for the next contraction. However, decreased SERCA2a expression and/or pump activity are key features in HF. As a result, there is a growing interest in developing therapeutic approaches to target SERCA2a. This review provides an overview of the regulatory mechanisms of the SERCA2a pump and explores potential strategies for SERCA2a-targeted therapy, which are being investigated in both preclinical and clinical studies.